2020
DOI: 10.21470/1678-9741-2019-0436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the operative and postoperative effects of del Nido and blood cardioplegia solutions in cardiopulmonary bypass surgery

Abstract: Objective Our goal was to compare the operative and postoperative effects of del Nido cardioplegia (DN group) and blood cardioplegia (BC group) performed in cardiac surgery. Methods A total of 83 patients were included, separated into DN group and BC group. The operative and postoperative effects of the two groups were compared for the first 24 hours until extubation. The operative and postoperative complete blood count (CBC), biochemical values and clinical parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Forty-one studies regarding DNC versus CC for myocardial protection used in adult cardiac surgery were included in the final analysis. 7,8,2058 On the basis of 9 retrospective observational studies we had previously included, another 32 studies published after September 2016 were included. Four of these studies were randomized controlled trials (RCTs), 24,36,39,43 one was a prospective observational study 20 while the rest were retrospective observational studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-one studies regarding DNC versus CC for myocardial protection used in adult cardiac surgery were included in the final analysis. 7,8,2058 On the basis of 9 retrospective observational studies we had previously included, another 32 studies published after September 2016 were included. Four of these studies were randomized controlled trials (RCTs), 24,36,39,43 one was a prospective observational study 20 while the rest were retrospective observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-eight and 39 studies respectively involving 21,391 and 21,595 patients reported CPB 7,8,2031,33,3542,4458 and ACC time. 7,8,2033,3542,44…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the dNCS has been used in pediatric surgery centers for many years, it has recently been used in adult cardiac surgery as well. The straightforward application of del Nido cardioplegia solution and its long-term effectiveness have increased its use in adult cardiac surgery [20]. In addition, it has been shown to provide 9,300 dollars of cost advantage in 100 cases [21].…”
Section: Del Nido Cardioplegia Solution (Dncs)mentioning
confidence: 99%
“…It can be administered antegradely or retrogradely. Additional doses of the dNCS may be given in patients with aortic insufficiency, hypertrophic hearts, coronary disease and in cases where the effectiveness of the given dose is insufficient [20].…”
Section: Del Nido Cardioplegia Solution (Dncs)mentioning
confidence: 99%